Analisis Komparatif Non Performing Financing (NPF) Perbankan Syariah Indonesia - Edy Junaedi (STAI Asy-Syukriyyah, 2017)
Purpose – The purpose of this paper is to identify performance between the Sharia Commercial Bank (SCB) and Sharia Business Unit (SBU) in Indoneia islamic banking industry, especially Non Performing Financing Design – the study uses survey based methodology for data collection, using Statistic Islamic Banking Industry from Otoritas Jasa Keuangan, for the study consists of Islamic banking Industry 13 sharia commercial banks and 21 sharia business units with ROA, OER, FDR and NPF Gross. For analizyng the obtained data, the statistical methods of SPSS 22 multivariate regression and analyzing performance ratios both of them. Indonesia’s Islamic banking industry remained under pressure after experiencing limited growth, a rise in non-performing financing (NPF) and inefficiency still hampered the further development of the Islamic banking sector to drive the domestic Islamic finance industry including easing regulations on the loan-to-value (LTV) ratio, risk-weighted assets (RWA), NPF restructuring, and capital participation. to improve the competitiveness of Indonesia’s shariah-based banks which are still lagging considerably behind conventional banks Islamic banks continued to innovate to increase their market share through various creative ways. These include exploring opportunities to manage endowment funds (waqf) and entering into a mini master repurchase agreements with other shariah-based banks to increase liquidity. Finding – the study shown that performance SCB is 85,9 percent from independent variables were researched and performance of SBU is 86,8 percent from independent variables were researched. Compared Sharia Business Unit performance more better than Sharia Commercial Bank in ROA, NPF Gross, BOPO, progressive FDR more than 100 percent, but market share of sharia commercial bank up 70 percent, so Indonesia’s Islamic banking industry still under pressure even sharia business unit has good performance.